Stability analysis of construction machinery on various terrains - Singh, Raj Kishen (2017)
The evolution of construction machinery due to the rapid rise of technology has been on an expeditious growth these past decades. The newer generation of complex and sophisticated machines has provided construction companies with the means to complete projects quicker and efficiently. However, these heavy machines still require operators on hand for control. These operators are expose to the safety hazards imposed by these machines whenever construction operations are carried out. Thus, operators are required to have the necessary knowledge and skills to command these complex machines, and at the same time, follow the safety requirements of the construction projects. With the huge weight of responsibilities placed on these operators, the competencies of these operators has to be at an all-time high during the entire course of the construction project. To ease the workload on the operators, the automation of construction machinery has been researched on for the past years. This report will discuss on the processes taken on the automating of the rotary drilling rig, TR360DH, and further elaborate on the steps taken. The different components of the drilling rig, and the degrees of freedom each of these component provides for the machines will be explained. Specific sensory equipment will be touch upon to provide solutions on how these equipment can help to control the components, and the implementing of these sensory equipment into the drilling rig to automate it. These processes will provide a basic understanding on the key areas to look at for automating any type of machines and how to transit on to simulation studies for the automation process.